Encyclopedia of hurricanes, typhoons, and cyclones - Longshore, David (Chicago : Fitzroy Dearborn, 1998)
Contains alphabetically arranged entries that provide information about various aspects of cyclonic systems as they appear in science, history, and culture; and includes maps, chronologies, photographs, and comments from first-hand observers of hurricanes, typhoons, and cyclones.
Includes bibliographical references (p. 357-361) and index.
Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Adult.
Keywords: Cyclones -- Encyclopedias; Hurricanes -- Encyclopedias; Typhoons -- Encyclopedias; Cyclones -- Encyclopedias; Hurricanes -- Encyclopedias; Typhoons -- Encyclopedias